O6C-20-nor-salvinorin A is a stable and potent KOR agonist. Issue 16 (1st September 2018) - Hirasawa, Shun; Cho, Min; Brust, Tarsis F.; Roach, Jeremy J.; Bohn, Laura M.; Shenvi, Ryan A.
Graphical abstract: Abstract: Salvinorin A (SalA) is a potent and selective agonist of the kappa -opioid receptor (KOR), but its instability has frustrated medicinal chemistry efforts. Treatment of SalA with weak bases like DBU leads to C8 epimerization with loss of receptor affinity and signaling potency. Here we show that replacement of C20 with H and replacement of O6 with CH2 stabilizes the SalA scaffold relative to its C8 epimer, so much so that epimerization is completely supressed. This new compound, O6C-20-nor-SalA, retains high potency for agonism of KOR.